Maternal Behavior by Birth Order in Wild Chimpanzees (Pan troglodytes): Increased Investment by First-Time Mothers - Stanton, Margaret A. (2014)
Parental investment theory predicts that maternal resources are finite and allocated among offspring based on factors including maternal age and condition, and offspring sex and parity. Among humans, firstborn children are often considered to have an advantage and receive greater investment than their younger siblings. However, conflicting evidence for this “firstborn advantage” between modern and hunter-gatherer societies raises questions about the evolutionary history of differential parental investment and birth order. In contrast to humans, most non-human primate firstborns belong to young, inexperienced mothers and exhibit higher mortality than laterborns. In this study, we investigated differences in maternal investment and offspring outcomes based on birth order (firstborn vs. later-born) among wild chimpanzees (Pan troglodyte schweinfurthii). During the critical first year of life, primiparous mothers nursed, groomed, and played with their infants more than did multiparous mothers. Furthermore, this pattern of increased investment in firstborns appeared to be compensatory, as probability of survival did not differ by birth order. Our study did not find evidence for a firstborn advantage as observed in modern humans but does suggest that unlike many other primates, differences in maternal behavior help afford chimpanzee first-borns an equal chance of survival.